2008
DOI: 10.1152/ajpendo.00748.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl amiloride improves glucose homeostasis in mouse models of type 2 diabetes

Abstract: Dimethyl amiloride (DMA) enhances insulin secretion in the pancreatic beta-cell. DMA also enhances time-dependent potentiation (TDP) and enables TDP to occur in situations where it is normally absent. As we have demonstrated before, these effects are mediated in part through inhibition of neuronal nitric oxide synthase (nNOS), resulting in increased availability of arginine. Thus both DMA and arginine have the potential to correct the secretory defect in diabetes by enabling or enhancing TDP. In the current st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 69 publications
1
7
0
Order By: Relevance
“…While classical studies pioneered by Henquin and colleagues have elucidated that extracellular glucose induces acute/transient (e.g., 0-10 minutes) intracellular alkalinization, likely through HCO 3 --mediated transport mechanisms, previous work has mainly focused on the acute role of insulin secretagogues on islet pH i (64,65). Our current work builds on early studies that demonstrated β cell alkalinization in islets of multiple mouse models of T2DM and the corresponding enhancement of insulin secretion after administration of pH i -lowering agents (26,27). Interestingly, it was recently noted that chronic hyperglycemia in vitro induces β cell alkalinization (66).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…While classical studies pioneered by Henquin and colleagues have elucidated that extracellular glucose induces acute/transient (e.g., 0-10 minutes) intracellular alkalinization, likely through HCO 3 --mediated transport mechanisms, previous work has mainly focused on the acute role of insulin secretagogues on islet pH i (64,65). Our current work builds on early studies that demonstrated β cell alkalinization in islets of multiple mouse models of T2DM and the corresponding enhancement of insulin secretion after administration of pH i -lowering agents (26,27). Interestingly, it was recently noted that chronic hyperglycemia in vitro induces β cell alkalinization (66).…”
Section: Discussionmentioning
confidence: 94%
“…Electrogenic sodium bicarbonate cotransporter NBCe1 regulates pancreatic β cell function in type 2 diabetes to repress GSIS (25). Moreover, decreasing islet cell pH i with dimethyl amiloride was demonstrated to augment time-dependent potentiation of insulin secretion and improve glucose metabolism in T2DM rodent models (24,26,27).…”
Section: Introductionmentioning
confidence: 99%
“…Derivatives of amiloride have been reported to increase insulin secretion from β-cells in vitro and in vivo (30,31). In contrast, no association between propafenone and insulin secretion has been previously reported.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, amiloride and its derivatives have been reported to be effective in treating type 2 diabetes (Gunawardana et al. , 2008), Huntington's disease (Wong et al.…”
Section: Discussionmentioning
confidence: 99%